2019
DOI: 10.1007/s40264-019-00842-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness and Safety of Direct Oral Anticoagulants in Patients with Atrial Fibrillation: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: Background: There are no head-to-head randomized controlled trials comparing different direct oral anticoagulants (DOACs). Thus, we systematically reviewed and meta-analyzed observational studies assessing the comparative effectiveness and safety of DOACs for stroke prevention in patients with atrial fibrillation (AF). Methods:We systematically searched MEDLINE and EMBASE up to February 2019 for observational studies comparing head-to-head different DOACs in patients with AF. Two independent reviewers identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 50 publications
(191 reference statements)
1
18
1
1
Order By: Relevance
“…In addition, observational studies and meta-analyses comparing DOACs vs. warfarin indicate a lower risk of major bleeding with use of dabigatran and apixaban compared with use of rivaroxaban [47,[51][52][53][54]. Also, there are previous studies comparing effectiveness and safety of individual DOACs without using warfarin as indirect comparator [31,36,37,55,56]. One US study compared rivaroxaban and dabigatran treatment among elderly with NVAF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, observational studies and meta-analyses comparing DOACs vs. warfarin indicate a lower risk of major bleeding with use of dabigatran and apixaban compared with use of rivaroxaban [47,[51][52][53][54]. Also, there are previous studies comparing effectiveness and safety of individual DOACs without using warfarin as indirect comparator [31,36,37,55,56]. One US study compared rivaroxaban and dabigatran treatment among elderly with NVAF.…”
Section: Discussionmentioning
confidence: 99%
“…Previous comparisons of real-world data suggest that while rivaroxaban, dabigatran and apixaban have similar treatment effect regarding the risk of ischemic stroke, apixaban may be associated with a lower risk of major bleeding compared with the other two. [29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Previous independent studies have also come to similar conclusions, but in contrast, the present study provides the largest number of patients included to date and several subgroup analyses that have not been previously conducted, including the association of previous exposure to anticoagulants with the risk of bleeding. 53,54 Taken together, these results provide independent confirmation of the safety profile of DOACs in AF patients and raise new and important questions to define future projects.…”
Section: Discussionmentioning
confidence: 54%
“…Douros et al compared the risk of major bleeding between rivaroxaban and dabigatran through a meta-analysis that included 6 studies. The result showed that there was an increased bleeding risk for rivaroxaban versus dabigatran (HR 1.33; 95% CI: 1.20-1.47) [19].…”
Section: Discussionmentioning
confidence: 99%